Diseño de propuesta para la intervención del patrimonio cultural edificado de la Ciudad de Riobamba “Casona Familia Soxo - Cepeda Velata, Robinson Israel (2022)
This research addresses the importance of cultural heritage built in Riobamba, having as a case of study the mansion owned by the "Soxo’s" family, a home that is part of the historic center of the city, located on the streets August 10 and Magdalena Davalos. Through graphical analysis, rehabilitation concepts, enhancement and traditional construction systems oriented towards the conservation of the built heritage. Strategies are proposed for the conservation of the built cultural heritage, divided into three levels of intervention: Liberation, constructive rehabilitation and enhancement, same ones that will help us to give the building a new opportunity to be important for the city, recovering the importance that it had in the past and that today it has lost to the point of being considered an old house by its people who ignore the great architectural and historical wealth it possesses, being a living testimony of the evolution and development of the city.